PERDAGANGAN LADA DI LAMPUNG DALAM TIGA MASA (1653-1930) - Iim Imadudin (Patanjala: Journal of Historical and Cultural Research, 2016)
This article aims to reveal the dynamics of the pepper trade in Lampung in three political systems. The study uses historical method consists of heuristics, criticism, interpretation, and historiography. The struggle for influence in the region is created in the pattern of domination and subordination. Lampung as the pepper producer is under the influence of Banten, VOC, and the Dutch government. Thus, it is inevitable that there isthe economic exploitation in the relationship. The study shows that the dynamics of the pepper trade in Lampung cannot be separated from the various competing parties. The players are Sultanate of Banten, VOC, and the Dutch government. However, the role of local elites of Lampungis also taken into account. The waning of pepper trade, in addition to internal factors such as not optimal maintenance of pepper garden, also due to lower demand from the international market. The monopoly factor of the pepper trade by foreign powers also crushes the pepper trade system that has lasted long enough.